STRATEGI GURU DALAM MENGATASI KURANGNYA KERJASAMA TIM SISWA MELALUI PEMBELAJARAN KOLABORATIF BERBASIS PROYEK - Rifana Azzahra; Azzah Nur Laili; Alfan Nurngain (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study is motivated by the low level of students’ teamwork in learning, indicated by limited participation, weak communication, and unequal contribution in group work. This study aims to analyze the initial condition of students’ teamwork, identify its causal factors, and examine teachers’ strategies in overcoming the issue through project-based collaborative learning. This research employs a library research method by analyzing relevant books and national journal articles published between 2021 and 2026. The findings show that low teamwork is influenced by teacher-centered learning, limited communication skills, and lack of individual responsibility. The implementation of project-based collaborative learning improves students’ participation, communication, and responsibility through systematic learning stages. Therefore, this model is effective in addressing teamwork issues. The implication of this study suggests that teachers need to optimize project-based learning to enhance students’ collaborative skills continuously.